A case study of College English teachers' emotional experiences in the blended teaching context - Shi, Yu; Gu, Haibo; Wang, Qian (Frontiers in Psychology, 2023)
The current research on language teacher education has witnessed a surge in studies focusing on teacher emotions due to their recognized importance in teaching. However, limited efforts have been found to investigate the emotions of Chinese College English teachers in the blended teaching context. Exploring teacher emotions in this context can contribute to a better understanding of the factors that facilitate wider acceptance and effective implementation of blended teaching in the post-pandemic era in and beyond China. Hence, this qualitative case study aims to uncover the emotional experiences of four Chinese College English teachers and explore the causes of their emotions in the blended teaching context. Data for the study was primarily gathered through interviews and case documents. The findings indicate that teachers in Eastern China experienced more positive emotions than negative emotions in the blended teaching context, while teachers in Western China exhibited the reverse pattern. These emotions were caused by their continuous appraisal of the interaction between their personal goals and various ecological systems. The research findings underscore the crucial role of teacher emotion in blended teaching and provide implications for enhancing blended teaching practices.